Correlation between Grain Boundary Migration and Stress Corrosion Cracking of Alloy 600 in Hydrogenated Steam. (March 2020) - Volpe, L.; Burke, M.G.; Scenini, F.
Abstract: Solution-annealed Alloy 600 samples were tested under active load conditions in a superheated low pressure H2 -steam environment over a range of oxidising potentials relevant to Primary Water Stress Corrosion Cracking (PWSCC). Increased SCC susceptibility was observed for potentials the more reducing than the Ni/NiO transition where a deeper Preferential Intergranular Oxidation (PIO) occurred. Advanced microstructural analysis clearly showed that SCC initiated along the grain boundaries that exhibited Diffusion-Induced Grain Boundary Migration (DIGM), as well as enrichments in Al and Ti. Rather than the result of a single dominant mechanism, the initiation of SCC in Ni-base alloys involves the synergistic interactions between DIGM and the formation of Al- and Ti-enriched oxides, promoting PIO that can fracture with applied stress. Graphical abstract: Image, graphical abstract